ความพึงพอใจและความต้องการของอาจารย์และนักศึกษาต่อบริการสารสนเทศ ของห้องสมุดสถาบันการจัดการปัญญาภิวัฒน์ในการสนับสนุนการเรียนรู้ จากการทำงาน - อุนาวงค์, เบญจมาศ; แสนวา, ศุมรรษตรา; พันธุ์เมฆา, พวา (บรรณศาสตร์ มศว, 2018)
การวิจัยนี้มีวัตถุประสงค์เพื่อศึกษาและเปรียบเทียบความพึงพอใจและความต้องการบริการสารสนเทศห้องสมุดในสถาบันการจัดการปัญญาภิวัฒน์ในการสนับสนุนการเรียนรู้จากการทำงานของอาจารย์จำแนกตามตัวแปรกลุ่มคณะวิชา ประสบการณ์การสอน ของนักศึกษาระดับปริญญาตรีจำแนกตามตัวแปรเพศ กลุ่มคณะวิชา และชั้นปี และของนักศึกษาระดับปริญญาโทจำแนกตามตัวแปรเพศ และกลุ่มคณะวิชา กลุ่มตัวอย่างได้แก่ อาจารย์ จำนวน 201 คน นักศึกษาระดับปริญญาตรี จำนวน 450 คน และนักศึกษาระดับปริญญาโท จำนวน 259 คน เครื่องมือที่ใช้ในการวิจัย ได้แก่ แบบสอบถาม สถิติที่ใช้ในการวิเคราะห์ข้อมูล ได้แก่ ค่าร้อยละ ส่วนเบี่ยงเบนมาตรฐาน ค่า t- test และค่า F–test พบผลวิจัย ดังนี้ 1. อาจารย์ มีความพึงพอใจต่อบริการสารสนเทศโดยรวมอยู่ในระดับมาก เมื่อเปรียบเทียบความพึงพอใจตามตัวแปรกลุ่มคณะวิชาและประสบการณ์ ไม่พบความแตกต่างทั้ง 2 ตัวแปร ด้านความต้องการบริการสารสนเทศโดยรวมอาจารย์มีความต้องการอยู่ในระดับมากที่สุด เมื่อเปรียบเทียบความต้องการตามตัวแปรกลุ่มคณะวิชา พบว่าแตกต่างกันอย่างมีนัยสำคัญทางสถิติที่ระดับ .05 แต่ประสบการณ์การสอนพบว่าไม่แตกต่างกัน 2. นักศึกษาระดับปริญญาตรีมีความพึงพอใจต่อบริการสารสนเทศโดยรวมอยู่ในระดับมาก เมื่อเปรียบเทียบความพึงพอใจตามตัวแปรเพศและระดับชั้นปีพบว่าไม่แตกต่างกัน แต่กลุ่มคณะวิชาพบว่ามีความแตกต่างกันอย่างมีนัยสำคัญทางสถิติที่ .05 ด้านความต้องการต่อบริการสารสนเทศโดยรวมอยู่ในระดับมากที่สุด เมื่อเปรียบเทียบความต้องการตามตัวแปรกลุ่มคณะวิชา และชั้นปี พบว่ามีความแตกต่างอย่างมีนัยสำคัญทางสถิติที่ระดับ .05 ส่วนตัวแปรเพศพบว่าไม่แตกต่างกัน 3. นักศึกษาระดับปริญญาโท มีความพึงพอใจต่อบริการสารสนเทศโดยรวมอยู่ในระดับมาก เมื่อเปรียบเทียบ ความพึงพอใจตามตัวแปรกลุ่มคณะวิชาพบว่า แตกต่างกันอย่างมีนัยสำคัญทางสถิติที่ระดับ .05 ส่วนตัวแปรเพศพบว่า ไม่แตกต่างกัน ด้านความต้องการต่อบริการสารสนเทศ พบว่านักศึกษามีความต้องการต่อบริการสารสนเทศโดยรวมอยู่ในระดับมากที่สุด เมื่อเปรียบเทียบตามตัวแปรเพศ และกลุ่มคณะวิชา พบว่ามีความแตกต่างกันอย่างมีนัยสำคัญทางสถิติที่ระดับ .05 This research aims to examine lectures', undergraduate students' and graduate students' satisfaction level with information service provided by Panyapiwat Institute of Management Library to encourage them to learn from working and practicing. Also, this research aims to compare the demand for information service provided by Panyapiwat Institute of Management Library between 3 groups of populations, namely lecturers, undergraduate students, and graduate students. The information was examined based on subject variables. The participants in this study were 201 lecturers, 5,696 undergraduate students, and 259 graduate students in this institute. Research instrument was questionnaires. The descriptive and inferential statistics were analyzed by SPSS Program using percentage, standard deviation, T-test, and F-test calculator. Research findings implied that lecturers, undergraduate students, and graduate students were highly satisfied with overall information service provided. According to variables, it was found that lecturers from different education program revealed statistically significant difference at .05; lecturers from Business Administration, Food Business Management, and Management Science required more information service than those from Communication Arts, Liberal Arts, and Education Program. Different teaching experience, however, showed no significant different of overall requirement for information service. In other words, there was no difference among lecturers with different year of teaching. Requirement of information service among undergraduate students with different genders indicated no significant difference overall or gender did not affect the level of need for service. Different year of study, however, indicated statistically significant different at .05; Undergraduate students from different education program required overall statistically significant different level of information service at .05. The finding also indicated the different level of information service required by graduate students who had different genders. There was statistically significant different at .05; Female graduate students required more information service than male graduate students. There was statistically significant different between graduate students from different education programs at .05; graduate students from Engineering and Technology and Management Science required more information service than those from Business Administration Program.